Transition to democracy, real wages and productivity: The Turkish experience - Erol Taymaz; Ebru Voyvoda; Kamil Yılmaz (Koç University-TÜSIAD Economic Research Forum (ERF), 2021)
We analyze the behavior of plant-level real wages and productivity in Turkish manufacturing after the transition to democracy in 1987 and test whether wages under democracy causes productivity. The Turkish experience provides almost an experimental case: real wages in manufacturing increased by 120% in the 1987-93 period due to (exogenous) political changes, together with unprecedented total factor productivity and labor productivity growth. While these observations provide support for the "democracies pay higher wages" hypothesis, they also stimulate further evaluation of the consequences of such politically-motivated 'exogenous' wage hikes on economic performance. Our analysis shows that real wage hikes during the democratic transition forced firms to increase productivity to stay competitive. The findings also help explain why countries that undergo an orderly transition from autocracy to democracy may achieve rapid productivity gains.
Keywords: D24; E24; J24; P16; 330; Democratic transition; Real wages; Total factor productivity; Labor productivity; Labor unions; Efficiency wages; Long-run growth